Reduced bone density in patients with inflammatory bowel disease. (February 1997) - Bjarnason, I; Macpherson, A; Mackintosh, C; Buxton-Thomas, M; Forgacs, I; Moniz, C
Abstract : BACKGROUND: Reduced bone mineral density in patients with inflammatory bowel disease is thought to be due to disturbances in calcium homeostasis or the effects of corticosteroid treatment. AIMS: To assess the prevalence and mechanism of reduced bone mineral density in 79 patients with inflammatory bowel disease (44 with Crohn's disease, 35 with ulcerative colitis) who did not have significant risk factors for low bone densities. METHODS: Dual x ray absorptiometry was used to measure bone mineral density and serum and urinary markers of osteoblast (alkaline phosphatase, procollagen 1 carboxy terminal peptide and osteocalcin) and osteoclast (pyridinoline, deoxypyridinoline, and type 1 collagen carboxy terminal peptide) activities to assess bone turnover. RESULTS: There was a high prevalence of low bone mineral density (prevalence of T scores < -1.0 from 51%-77%; T scores < -2.5 (osteoporosis) from 17%-28%) with hips being more often affected than vertebrae (p < 0.001). Reduced bone mineral density did not relate to concurrent or past corticosteroid intake, or type, site, or severity of disease. Whereas calcium homeostasis was normal, bone markers showed increased bone resorption without a compensatory increase in bone formation. CONCLUSIONS: The greater prevalence of reduced hip bone mineral density, as opposed to vertebral, mineral density and the pattern of a selective increase in bone resorption contrasts with that found in other known causes of metabolic bone disease.